HUMAN PERSON PERSPECTIVES - Mannath, Joe (Journal of Dharma, 1996)
"The Human Person: Philosophical and Religious Perspectives" is the theme of this number of the Journal of Dharma. The articles in this issue were presented and discussed at the 1995 session of the Association of Christian Philosophers of India (ACPI).The theme needs neither introduction nor apology. Belonging as it does to the core of the philosophical and theological concerns of today (and not just of today), it has evident repercussions in a number of related fields, from ethics to inter-religious dialogue, from psychology to the East-West encounter. As is evident from the papers that follow, we looked at this central topic from a rich variety of perspectives - philosophical and religious, Eastern and Western'-and tried to integrate the valid insights of the various views into the necessarily incomplete and partial understanding that each of us possesses.